Pengaruh Kualitas Pelayanan Shopee PayLater Terhadap Keputusan Pengguna - Meilana Widyaningsih; Ayu Sekar Pratiwi; Safira Indita (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2022)
Financial transactions are growing rapidly, while still in its infancy. The purpose of this research is to find out how Surakarta residents are influenced by assurance, reliability, and empathy for Paylater users. authors can conduct further investigations and better understand how the use of Shopee Paylater in consumer purchasing decisions Electronic money is more and more often used together with card payments as we move towards a digital economy. Because technology has developed so quickly and easily, e-commerce businesses can now take advantage of opportunities to grow their customer base. Researchers concentrate on research topics involving customers who make online purchases in the Surakarta City area using Shopee PayLater. To select the sample size for this study, a purposive sampling technique was used, and individuals who were considered to have data sources that matched the research criteria were given questionnaires. The research design adopts a quantitative methodology using numerical data collection and analytical techniques. We use primary data to investigate how Surakarta residents are influenced by assurance, reliability, empathy, and paylater user behavior. To collect data, questionnaires were distributed to a total of 120 respondents. The results of simultaneous hypothesis testing reveal that, at least in part, while using the Shopee Paylater payment option, the characteristics of assurance, reliability, and empathy have a significant effect on purchasing decisions (Test F). The impact of certainty, reliability and empathy on user choices when using the Shopee Paylater payment option.